Risk Factors for HIV/Syphilis Infection and Male Circumcision Practices and Preferences among Men Who Have Sex with Men in China. (30th March 2014) - Zeng, Yali; Zhang, Linglin; Li, Tian; Lai, Wenhong; Jia, Yujiang; Aliyu, Muktar H.; Do, Mai; Wang, Xiaodong; Han, Delin; Huang, Wanli; Du, Shuping; Xu, Jie; et al.
Abstract : Objective . To investigate factors associated with HIV infection and the frequency and willingness of male circumcision among men who have sex with men (MSM) in Chengdu city, China. Methods . A cross-sectional survey provided information on participants' demographics, risk behaviors, circumcision, and uptake of HIV prevention services. Results . Of 570 participants, 13.3% were infected with HIV and 15.9% with syphilis. An estimated 43.0% of respondents reported having unprotected receptive anal intercourse, and 58.9% reported having ≥2 male sexual partners in the past 6 months. Multivariable logistic regression revealed that syphilis, more male sex partners, predominantly receptive anal intercourse, and exclusively receptive male sex were associated with HIV infection. Higher level of education and peer education service were inversely associated with HIV infection. Nearly a fifth (18.0%) of participants were circumcised. More than half of uncircumcised participants expressed willingness to be circumcised. Conclusion . This study reveals a high prevalence of HIV and syphilis among MSM in Chengdu province of China. The frequency of unprotected receptive anal intercourse and multiple male sexual partnerships highlight the urgency for an effective comprehensive HIV prevention strategy. Although the willingness to accept male circumcision (MC) is high, further research is needed to assess the protective effective of MC among MSM.